Studi Bentuk Dan Fungsi Ruang Pada Istana Raja (Sonaf) Di Desa Oelolok Kecamatan Insana Kabupaten Kefamenanu â Nusa Tenggara Timur - Andereas Pandu Setiawan, Rifaldy Aditya Dethan (Intra, 2014)
First of all, the palace is the official residence of the king (a head of state or a president) and his family. As we know, that the king is the supreme ruler of the kingdom (usually acquired as inheritance); a person, who is in charge to rule a nation or state. So, the place where he lives should be a majestic place. Many palaces anywhere but it impossible for palaces to have the same design and form.Â  Similarly, East Nusa Tenggara in the ancient time, it was well known as a region with kingdom era. It was recognized by an ancient buildings, which were occupied by the ancient king as his home that called the Palace. Those buildings do not have the same form and design. Thus, this study will examine the form and function of the space as this study is expected to broaden the publicâs insight about the form and function of an existing palace.